Metagenomics of African Empogona and Tricalysia (Rubiaceae) reveals the presence of leaf endophytes - Brecht Verstraete; Steven Janssens; Petra De Block; Pieter Asselman; Gabriela Méndez; Serigne Ly; Perla Hamon; Romain Guyot (PeerJ, 2023)
Background Leaf symbiosis is a phenomenon in which host plants of Rubiaceae interact with bacterial endophytes within their leaves. To date, it has been found in around 650 species belonging to eight genera in four tribes; however, the true extent in Rubiaceae remains unknown. Our aim is to investigate the possible occurrence of leaf endophytes in the African plant genera Empogona and Tricalysia and, if present, to establish their identity. Methods Total DNA was extracted from the leaves of four species of the Coffeeae tribe (Empogona congesta, Tricalysia hensii, T. lasiodelphys, and T. semidecidua) and sequenced. Bacterial reads were filtered out and assembled. Phylogenetic analysis of the endophytes was used to reveal their identity and their relationship with known symbionts. Results All four species have non-nodulated leaf endophytes, which are identified as Caballeronia. The endophytes are distinct from each other but related to other nodulated and non-nodulated endophytes. An apparent phylogenetic or geographic pattern appears to be absent in endophytes or host plants. Caballeronia endophytes are present in the leaves of Empogona and Tricalysia, two genera not previously implicated in leaf symbiosis. This interaction is likely to be more widespread, and future discoveries are inevitable.